Prostate cancer proliferation is affected by the subcellular localization of MCT2 and accompanied by significant peroxisomal alterations - Valença, I (2020)
Reprogramming of lipid metabolism directly contributes to malignant transformation and progression. The increased uptake of circulating lipids, the transfer of fatty acids from stromal adipocytes to cancer cells, the de novo fatty acid synthesis, and the fatty acid oxidation support the central role of lipids in many cancers, including prostate cancer (PCa). Fatty acid ß-oxidation is the dominant bioenergetic pathway in PCa and recent evidence suggests that PCa takes advantage of the peroxisome transport machinery to target monocarboxylate transporter 2 (MCT2) to peroxisomes in order to increase ß-oxidation rates and maintain the redox balance. Here we show evidence suggesting that PCa streamlines peroxisome metabolism by upregulating distinct pathways involved in lipid metabolism. Moreover, we show that MCT2 is required for PCa cell proliferation and, importantly, that its specific localization at the peroxisomal membranes is essential for this role. Our results highlight the importance of peroxisomes in PCa development and uncover different cellular mechanisms that may be further explored as possible targets for PCa therapy.